Laparoscopic Gastric Sleeve and Micronutrients Supplementation: Our Experience. (22nd March 2012) - Capoccia, D.; Coccia, F.; Paradiso, F.; Abbatini, F.; Casella, G.; Basso, N.; Leonetti, F.
Abstract : Background . Laparoscopic gastric sleeve (LGS) has been recently introduced as a stand-alone, restrictive bariatric surgery. Theoretically, LGS attenuates micronutrients deficiencies and associated complications that were typically observed following malabsorptive procedures. The aim of this study was to assess some micronutrients and mineral deficiencies in patients undergoing LGS. Methods . In the period between July 2008 and April 2010, 138 obese patients (110 females and 28 males) with mean BMI 44.4 kg/m 2 ± 6.5, mean age 43.9 ± 10.9 years were enrolled and underwent LGS. Patients were followed up with routine laboratory tests and anthropometric measurements and assessed for nutritional status, as regards vitamin B12, folic acid, iron, hemoglobin, calcium, and vitamin D, every three months throughout 12 months. Results . 12 months after sleeve, patients did not show iron deficiency and/or anemia; plasma calcium levels were in the normal range without supplementation from the sixth month after the operation. Vitamin B12 and folic acid were adequately supplemented for all the follow-up period. Vitamin D was in suboptimal levels, despite daily multivitamin supplementation. Conclusion . In this study, we showed that LGS is an effective surgery for the management of morbid obesity. An adequate supplementation is important to avoid micronutrients deficiencies and greater weight loss does not require higher dosage of multivitamins.